2003
DOI: 10.1002/ls.3010150202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lubricant viscosity on the mixed lubrication of a piston ring pack in an internal combustion engine

Abstract: A theoretical analysis is presented of the mixed lubrication of a piston ring pack. The analysis comprises Patir and Cheng's average flow model and Greenwood and Tripp's asperity interaction model, and is developed to consider the shear thinning effect of a non‐Newtonian fluid, multigrade lubricant. The friction characteristics of the piston ring pack for both monograde and multigrade lubricants are investigated. It is found that a decrease in the lubricant viscosity is effective in reducing the friction loss,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Later on, these results were used by the same authors to make predictions about the friction in the mixed lubrication regime. Hamatake et al 6,7 showed that the piston ring friction was influenced by a kind of lubricant oil when contact occurred in the mixed lubrication regime. In addition to this element, the effects on the friction forces of the lubrication conditions (starved and pure hydrodynamic) were analytically examined of a piston ring pack.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, these results were used by the same authors to make predictions about the friction in the mixed lubrication regime. Hamatake et al 6,7 showed that the piston ring friction was influenced by a kind of lubricant oil when contact occurred in the mixed lubrication regime. In addition to this element, the effects on the friction forces of the lubrication conditions (starved and pure hydrodynamic) were analytically examined of a piston ring pack.…”
Section: Introductionmentioning
confidence: 99%
“…However, another more accurate fit over wider temperature rage 33,34 is Vogel equation 35 (equation (4)). The Vogel equation is widely used in PRL lubrication models 28,29,3638 and is expressed as follows
Figure 3.Temperature-dependent viscosity variation of two different SAE-indexed multigrade oils.
…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Artificial surface modification such as honing is not considered in the present study; thus, as supposed by previous studies, 29,36,44 δ is assumed to follow the Gaussian distribution in the current work. Therefore, h T is expressed as follow 36 where σ=σ1 2+σ2 2.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…In recent years, many results have been achieved. For example, Harigaya [1], Hamatake [2], Froelund, K [3], Ejakov [4], Hamatake, Toshiro [5], Toshiro and Y [6] Harigaya have studied the effects of lubricant viscosity on the film thickness and friction force of piston ring-cylinder liner components. TIAN [7][8] and the research impact of the dynamics of piston and piston ring set on the effect of friction and lubrication.…”
Section: Introductionmentioning
confidence: 99%